Glass ceramic capable of being subjected to 3D hot bending as well as preparation method and application of glass ceramic
Through the microcrystalline glass prepared by the first crystallization method, the crystal composition of lithium long stone, lithium silicate and quartz is controlled, solving the problem of poor microcrystalline glass mechanical properties and 3D molding in the existing technologies, and realized the white appearance, which realizes the white appearance. 3D microcrystalline glass with good mechanical performance and size stability.
Patent Information
- Application Number
- CN202410417328.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-08
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-04-08
AI Technical Summary
The existing methods for preparing white cover glass lead to the large grain size of the microcrystalline glass, resulting in cracks, high thermal expansion and softening points, deterioration of mechanical properties, and inability to perform 3D molding.
Micro crystal glass is prepared through the first crystallization method, and the composition of crystal phase is controlled, including lithium long stone, lithium silicate and quartz. The total crystal content is 40-70%, and the sum of the content of lithium long stone and di siliconicate accounts for 50 -70%, the content of quartz crystal phase accounts for 4-10%, and improves the mechanical properties and size stability of glass through nucleification and crystallization.
The 3D thermal curvature of microcrystalline glass is achieved, maintaining a white appearance, improving mechanical performance and size stability, and can prepare 3D micro -crystal glass and processing into three -dimensional products.
Smart Images

Figure CN119371105A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of microcrystalline glass materials, and relates to a 3D heat-bendable microcrystalline glass and a preparation method and application thereof. Due to its pleasing white appearance, good mechanical properties and dimensional stability, it is particularly suitable as an external component of portable communication equipment or information equipment. Background Art
[0002] The shells of electronic devices such as mobile phones are usually made of polymer materials, ceramic materials, etc., considering various factors such as decorativeness, scratch resistance, processability or cost. The shells of portable terminal devices are mostly made of composite materials such as plastics and resins. However, when plastics, resins and other materials are used to form the shell, there are problems such as poor heat dissipation and easy scratches; when ceramics and other materials are used to form the shell, there are problems such as high density, poor impact resistance, and increased weight of the mobile phone.
[0003] Glass-ceramics is a type of composite material that contains both glass phase and microcrystalline phase and is prepared by targeted controlled heat treatment of the base glass. It mainly utilizes the crystalline phase precipitated inside the glass-ceramics to hinder the expansion of microcracks, thereby increasing the fragility of the glass to a certain extent. Compared with ordinary glass materials, glass-ceramics has better mechanical properties; compared with plastics, it has good heat resistance, is not easy to age and is scratch-resistant; compared with ceramic materials, it has the advantages of lower density and lighter weight. In addition, glass-ceramics can obtain rich and colorful colors through composition and process control, showing a colorful appearance, thus becoming the best choice for cover materials of portable electronic devices on the market.
[0004] However, the existing method of preparing white cover glass can make glass-ceramics into translucent glass with large grain size through secondary recrystallization and have white color; however, the translucent white glass has large grain size, which leads to cracks, high thermal expansion softening point, poor mechanical properties such as hot bending and falling, and inability to perform 3D molding. In addition, as a mobile phone back panel material, the deformation of glass-ceramics must also be considered. Large deformation is easy to damage the internal components of the terminal. Therefore, the art needs a glass-ceramic material with a pleasing white appearance, good mechanical properties and dimensional stability, and three-dimensional processability. Summary of the invention
[0005] In response to the above-mentioned problems, the present application provides a 3D heat-bendable microcrystalline glass and a preparation method thereof. The 3D heat-bendable microcrystalline glass is prepared through primary crystallization and has a pleasing white appearance, good mechanical properties and dimensional stability, and can be processed into three-dimensional products, and has good processability.
[0006] Specifically, this application provides the following technical solutions:
[0007] In a first aspect, the present application provides a 3D heat-bendable microcrystalline glass, characterized in that the crystalline phases of the 3D heat-bendable microcrystalline glass include petalite crystalline phase, lithium disilicate crystalline phase and quartz crystalline phase, and the total crystalline phase content of the 3D heat-bendable microcrystalline glass is 40-70%, wherein the sum of the contents of the petalite crystalline phase and the lithium disilicate crystalline phase accounts for 50-70% of the total crystalline phase content, and the content of the quartz crystal phase accounts for 4-10% of the total crystalline phase content.
[0008] In some embodiments of the present application, in the 3D heat-bendable glass-ceramics, the quartz crystal phase is β-quartz; and / or,
[0009] The 3D heat-bendable glass-ceramics further comprises a lithium silicate crystal phase, and preferably the content of the lithium silicate crystal phase accounts for 20-40% of the total crystal phase content; and / or,
[0010] The crystal phase of the 3D heat-bendable glass-ceramics further includes a spodumene crystal phase; preferably, the content of the spodumene crystal phase accounts for 0-11% of the total crystal phase content.
[0011] In some embodiments of the present application, the grain size of the 3D heat-bendable glass-ceramics is 20-40 nm;
[0012] And / or, the expansion softening point of the 3D heat-bendable glass-ceramics is less than or equal to 810° C.;
[0013] And / or, when the 3D heat-bendable glass-ceramics has a thickness of 0.60 mm, the light transmittance at 550 nm is between 30% and 50%;
[0014] And / or, the color coordinates of the 3D heat-bendable micro-ceramic glass in the reflection mode are: L* is 70 to 82, a* is -4 to 2, and b* is -12 to 5.
[0015] In some embodiments of the present application, the composition comprises, in terms of the content expressed as a molar percentage of the oxide:
[0016] SiO2: 60~73%,
[0017] Al2O3: 4~6%,
[0018] P2O5: 0~2%,
[0019] ZrO2: 1~3%,
[0020] Na2O: 0.1~4%,
[0021] K2O: 0~1%,
[0022] Li2O: 14-23%,
[0023] CaO: 0~1.5% and
[0024] B2O3: 0.1~5%.
[0025] In some embodiments of the present application, the composition comprises, in terms of the content expressed as a molar percentage of the oxide:
[0026] SiO2: 60~73%,
[0027] Al2O3: 4~6%,
[0028] P2O5: 0~2%,
[0029] ZrO2: 1~3%,
[0030] Na2O: 1~4%,
[0031] K2O: 0~1%,
[0032] Li2O: 14-23%,
[0033] CaO: 0~1.5% and
[0034] B2O3: 1~5%.
[0035] In some embodiments of the present application, the 3D heat-bendable microcrystalline glass is prepared by subjecting the substrate glass to nucleation and crystallization treatments.
[0036] In a second aspect, the present application further provides a method for preparing the above-mentioned 3D heat-bendable microcrystalline glass, the preparation method comprising the following steps:
[0037] Step 1: Mix the raw materials for preparing glass, melt them, cool them and perform annealing to obtain the substrate glass;
[0038] Step 2: performing a nucleation treatment on the substrate glass obtained in step 1;
[0039] Step 3: Crystallize the substrate glass after nucleation in the above step 2 to obtain the microcrystalline glass that can be 3D hot-bent.
[0040] In some embodiments of the present application, in step 1 of the above preparation method, the melting temperature is 1350-1700°C, preferably the melting temperature is 1400-1650°C, and more preferably cooled to 500-1000°C after melting.
[0041] In some embodiments of the present application, in step 2 of the above preparation method, the temperature of the nucleation treatment is 520-590° C., and the nucleation treatment time is preferably 30-600 min; and / or,
[0042] In step 3, the temperature of the crystallization treatment is 640-750° C., and the preferred crystallization treatment time is 20-600 min.
[0043] In a third aspect, the present invention further provides a 3D microcrystalline glass, which is prepared by subjecting the above-mentioned 3D heat-bendable microcrystalline glass or the 3D heat-bendable microcrystalline glass obtained by the above-mentioned preparation method to a 3D heat bending process.
[0044] In some embodiments of the present application, the 3D microcrystalline glass includes a petalite crystal phase, a lithium disilicate crystal phase and a quartz crystal phase, and the total crystal phase content is 60-90%, wherein the sum of the contents of the petalite crystal phase and the lithium disilicate crystal phase accounts for 45-60% of the total crystal phase content, and the content of the quartz crystal phase accounts for 15-22% of the total crystal phase content.
[0045] In some embodiments of the present application, the quartz crystal phase is β-quartz,
[0046] And / or, the 3D glass-ceramics further comprises a lithium silicate (Li2SiO3) crystal phase, and preferably the content of the lithium silicate crystal phase accounts for 20-40% of the total crystal phase content;
[0047] And / or, the crystal phase of the 3D glass-ceramics further includes a spodumene crystal phase; preferably, the content of the spodumene crystal phase accounts for 0-15% of the total crystal phase content.
[0048] In some embodiments of the present application, the grain size of the 3D glass-ceramics is 35-50 nm;
[0049] And / or, when the 3D glass-ceramics has a thickness of 0.60 mm, the light transmittance at 550 nm is between 15% and 35%;
[0050] And / or, the color coordinates of the 3D glass-ceramics in the reflection mode are: L* is 70 to 81, a* is -2.60 to 0.00, and b* is -7 to 1;
[0051] And / or, the X-axis shrinkage of the 3D glass-ceramics is less than or equal to 1%, preferably less than or equal to 0.5%; preferably, the Y-axis shrinkage of the 3D glass-ceramics is less than or equal to 0.5%, preferably less than or equal to 0.35%;
[0052] And / or, the single-rod static pressure strength of the 3D microcrystalline glass is greater than 320N.
[0053] In a fourth aspect, the present application also provides a 3D microcrystalline glass product, which is obtained by chemically strengthening the above-mentioned 3D microcrystalline glass.
[0054] In a fifth aspect, the present application also provides an electronic device, which comprises the above-mentioned heat-bendable microcrystalline glass or the heat-bendable microcrystalline glass obtained by the above-mentioned preparation method or the above-mentioned 3D microcrystalline glass or the above-mentioned 3D microcrystalline glass product; preferably, the electronic device includes a mobile phone, a tablet computer, a laptop computer, a television or a display device; more preferably, the heat-bendable microcrystalline glass or the 3D microcrystalline glass is the shell of the electronic device or a part of the shell, preferably the back panel or a part of the back panel of the electronic device.
[0055] In a sixth aspect, the above-mentioned 3D heat-bendable microcrystalline glass or the 3D heat-bendable microcrystalline glass obtained by the above-mentioned preparation method or the above-mentioned 3D microcrystalline glass or the above-mentioned 3D microcrystalline glass product is used in electronic devices, preferably in the casing of electronic devices, and more preferably in the back panel of a mobile phone.
[0056] Beneficial effects of the present invention:
[0057] 1. The present application controls the 3D hot-bendable microcrystalline glass to generate quartz grains by primary crystallization before hot bending, and the size and volume are controllable, so that the glass appears white (white appearance as shown by the L*a*b* value) and has good mechanical properties, ensuring that it can be 3D hot-bent at 810°C, and can prepare 3D microcrystalline glass and process it into three-dimensional products.
[0058] 2. The present application controls the crystal phase composition of the 3D heat-bendable microcrystalline glass so that it continues to crystallize during the heat bending process, and controls the proportion of each crystal phase after the heat bending process, especially the proportion of the quartz crystal phase, within an appropriate range, so that the prepared 3D microcrystalline glass still has a white appearance and good mechanical properties and dimensional stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 This is a thermal expansion coefficient curve of the white microcrystalline glass in Example 3.
[0060] Figure 2 This is a picture of the white glass-ceramics prepared in Example 3 after being heat-bent at 810°C.
[0061] Figure 3 This is a picture of the white microcrystalline glass prepared in Comparative Example 2 after being heat-bent at 810°C.
[0062] Figure 4 This is a scanning electron microscope image of the glass-ceramics of Example 3 before heat bending.
[0063] Figure 5 This is a scanning electron microscope image of the glass-ceramics of Example 3 after heat bending.
[0064] Figure 6This is a scanning electron microscope image of the glass-ceramic of Comparative Example 2 before heat bending.
[0065] Figure 7 This is a scanning electron microscope image of the glass-ceramic of comparative example 5 before heat bending.
[0066] Figure 8 This is a scanning electron microscope image of the microcrystalline glass of comparative example 5 after heat bending.
[0067] Fig. 9 These are the XRD patterns of the white glass-ceramics of Example 3 before and after hot bending.
[0068] Fig.10 This is the XRD spectrum of the white microcrystalline glass of comparative example 2 before hot bending.
[0069] Fig.11 This is the XRD spectrum of the white microcrystalline glass of comparative example 5 before and after hot bending. DETAILED DESCRIPTION
[0070] In the present invention, unless otherwise specified in specific circumstances, the numerical ranges listed herein include upper and lower limits, and "above" and "below" include the endpoint values, as well as all integers and fractions within the range, and are not limited to the specific values listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A; and / or B" means only A, or only B, or both A and B.
[0071] In a first aspect, the present application provides a 3D heat-bendable microcrystalline glass, wherein the crystalline phase of the 3D heat-bendable microcrystalline glass comprises petalite (LiAlSi4O 10 ) crystal phase, lithium disilicate (Li2Si2O5) crystal phase and quartz crystal phase, the total crystal phase content of the 3D heat-bendable microcrystalline glass is 40-70%, wherein the sum of the contents of petalite crystal phase and lithium disilicate crystal phase accounts for 50-70% of the total crystal phase content, and the content of quartz crystal phase accounts for 4-10% of the total crystal phase content.
[0072] In some embodiments of the present application, the total crystalline content of the 3D heat-bendable glass-ceramics is 40-70%, preferably 45-60%. In some embodiments of the present application, the total crystalline content of the 3D heat-bendable glass-ceramics can be 40%, 42%, 43%, 45%, 48%, 50%, 55%, 60%, 65%, 68% or 70%; or within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0073] In some embodiments of the present application, the quartz crystal phase is β-quartz. In some embodiments of the present application, the content of the quartz crystal phase in the 3D heat-bendable microcrystalline glass may account for 4-10%, 4-9%, 4-8%, 5-10%, 6-10% or 7-10% of the total crystal phase content. In some embodiments of the present application, the content of the quartz crystal phase may account for 4%, 5%, 6%, 7%, 8%, 9% or 10% of the total crystal phase content, or be within the numerical range consisting of any two of the above specific values as endpoints. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges.
[0074] It should be noted that the A crystal phase + B crystal phase ratio mentioned in the present application refers to the percentage of the sum of the crystal phase contents of the A crystal phase + the B crystal phase in the total crystal phase content of the microcrystalline glass; the C crystal phase ratio is the percentage of the crystal phase content of the C crystal phase in the total crystal phase content of the microcrystalline glass; the D crystal phase ratio is the percentage of the crystal phase content of the D crystal phase in the total crystal phase content of the microcrystalline glass; the E crystal phase ratio is the percentage of the crystal phase content of the E crystal phase in the total crystal phase content of the microcrystalline glass.
[0075] In some embodiments of the present application, the 3D heat-bendable microcrystalline glass also includes a lithium silicate (Li2SiO3) crystal phase. In some embodiments of the present application, the content of the lithium silicate (Li2SiO3) crystal phase may account for 20-40%, 22-38%, 22-36%, 22-34%, 22-32%, 22-30%, 24-40%, 26-40%, 28-40% or 30-40% of the total crystal phase content. In some embodiments of the present application, the content of the lithium silicate (Li2SiO3) crystal phase may account for 20%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 34%, 36%, 38% or 40% of the total crystal phase content; or it is within the numerical range consisting of any two of the above specific values as endpoints. It should be understood that in specific embodiments, any of the above ranges may be combined with any other ranges.
[0076] In some embodiments of the present application, the petalite (LiAlSi4O 10 ) crystalline phase and lithium disilicate (Li2Si2O5) crystalline phase may account for 50-70%, 50-68%, 50-66%, 50-64%, 50-62%, 50-60%, 52-70%, 54-70%, 56-70%, 58-70% or 60-70% of the total crystalline phase content. In some embodiments of the present application, petalite (LiAlSi4O 10The sum of the contents of the crystalline phase and the lithium disilicate (Li2Si2O5) crystalline phase may account for 50%, 52%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 62%, 64%, 66%, 68% or 70% of the total crystalline phase content, or be within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges.
[0077] In some embodiments of the present application, the crystalline phase of the 3D heat-bendable glass-ceramics also includes a spodumene (LiAlSi2O6) crystalline phase. In some embodiments of the present application, the content of the spodumene crystalline phase in the 3D heat-bendable glass-ceramics may account for 0-11%, 1-11%, 3-11%, 5-10%, 3-9% or 6-9% of the total crystalline phase content. In some embodiments of the present application, the content of the spodumene (LiAlSi2O6) crystalline phase may account for 0%, 1%, 2%, 3%, 5%, 8%, 10% or 11% of the total crystalline phase content; or it may be within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges.
[0078] In some embodiments of the present application, the average grain size of the 3D heat-bendable glass-ceramics is 20-40nm, preferably 25-38nm. In some embodiments of the present application, the average grain size of the 3D heat-bendable glass-ceramics can be 20nm, 23nm, 25nm, 27nm, 28nm, 30nm, 32nm, 34nm, 35nm, 37nm, 38nm or 40nm, or within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0079] In the present application, the thickness t of the 3D heat-bendable glass-ceramics is not particularly limited, for example, it can be 0.4 to 2.0 mm; preferably 0.4 to 1.0 mm. In some embodiments of the present application, the thickness t of the 3D heat-bendable glass-ceramics can be 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 2.0 mm, or a range formed by any two of the above values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0080] In some embodiments of the present application, the expansion softening point of the 3D heat-bendable glass-ceramics is less than or equal to 810°C; preferably 650°C-810°C. In some embodiments of the present application, the expansion softening point of the 3D heat-bendable glass-ceramics may be 650°C, 670°C, 690°C, 700°C, 720°C, 750°C, 770°C, 780°C, 790°C, 800°C, 805°C or 810°C, or within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges.
[0081] In some embodiments of the present application, the 3D heat-bendable glass-ceramics has a light transmittance of 30-50% at a wavelength of 550nm when the thickness is 0.60mm. In some embodiments of the present application, the 3D heat-bendable glass-ceramics has a light transmittance of 30%, 35%, 38%, 40%, 43%, 45%, 48% or 50% at a wavelength of 550nm when the thickness is 0.60mm, or is within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges.
[0082] In some embodiments of the present application, the color coordinates of the 3D heat-bendable microcrystalline glass in the reflection mode are: L* is 70~82, a* is -4~2, and b* is -12.00~5.00; preferably, the color coordinates of the 3D heat-bendable microcrystalline glass in the reflection mode are L* is 72~82, a* is -3.62~4, and b* is -11.31~4.00; more preferably, the color coordinates of the 3D heat-bendable microcrystalline glass in the reflection mode are L* is 74~80, a* is -3.00~3.00, and b* is -10.00~3.00.
[0083] In some embodiments of the present application, the composition of the 3D heat-bendable glass-ceramics contains, in terms of molar percentage of oxides:
[0084] SiO2: 60~73%,
[0085] Al2O3: 4~6%,
[0086] P2O5: 0~2%,
[0087] ZrO2: 1~3%,
[0088] Na2O: 0.1~4%,
[0089] K2O: 0~1%,
[0090] Li2O: 14-23%,
[0091] CaO: 0~1.5% and
[0092] B2O3: 0.1~5%.
[0093] Preferably, the composition of the 3D heat-bendable glass-ceramics contains, in terms of molar percentage of oxides:
[0094] SiO2: 60~73%,
[0095] Al2O3: 4~6%,
[0096] P2O5: 0~2%,
[0097] ZrO2: 1~3%,
[0098] Na2O: 1~4%,
[0099] K2O: 0~1%,
[0100] Li2O: 14-23%,
[0101] CaO: 0~1.5% and
[0102] B2O3: 1~5%.
[0103] SiO2 is an oxide that forms a glass network skeleton, which is used to stabilize the network structure of glass and microcrystalline glass. In the lithium aluminum silicon system, it is used to form crystalline phases such as lithium silicate, petalite and quartz. In some embodiments of the present application, in terms of the molar percentage of oxides, the 3D heat-bendable microcrystalline glass includes 60.00-73.00 mol%, 60.00-72.00 mol%, 60.00-71.00 mol%, 60.00-70.00 mol%, 60.00-69.00 mol%, 60.00-68.00 mol%, 60.00-67.00 mol%, 60.00-66.00 mol%, 60.00-68.00 mol%, 60.00-69 ... 5.00 mol%, 61.00-73.00 mol%, 62.00-73.00 mol%, 63.00-73.00 mol%, 64.00-73.00 mol%, 65.00-73.00 mol%, 66.00-73.00 mol%, 67.00-73.00 mol%, 68.00-73.00 mol%, 69.00-73.00 mol% or 70.00-73.00 mol% SiO2. In some embodiments of the present application, the 3D heat-bendable glass-ceramics includes 60.00mol%, 61.00mol%, 62.00mol%, 63.00mol%, 64.00mol%, 65.00mol%, 66.00mol%, 67.00mol%, 68.00mol%, 69.00mol%, 70.00mol%, 71.00mol%, 72.00mol% or 73.00mol% SiO2, or SiO2 within a numerical range consisting of any two of the above specific values as endpoints, in terms of molar percentage of oxide. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0104] Al2O3 is used to form a glass skeleton and is an indispensable component for forming petalite. In some embodiments of the present application, the 3D heat-bendable microcrystalline glass includes 4.00-6.00mol%, 4.50-6.00mol%, 5.00-6.00mol%, 4.00-5.50mol or 4.00-5.00mol% Al2O3 in terms of the molar percentage of the oxide. In some embodiments of the present invention, the 3D heat-bendable microcrystalline glass includes 4.00mol%, 4.10mol%, 4.20mol%, 4.50mol%, 4.60mol%, 4.70mol%, 4.80mol%, 5.00mol%, 5.50mol%, 5.70mol%, 5.80mol%, 5.90mol% or 6.00mol% Al2O3 in terms of the molar percentage of the oxide; or Al2O3 within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in specific embodiments, any of the above ranges may be combined with any other ranges.
[0105] P2O5 is a glass-forming oxide. It exists in the network structure as phosphorus-oxygen tetrahedrons [PO4]. It can perform non-uniform nucleation in the glass, promote crystal formation, and help improve the uniformity of the microcrystalline glass, and improve the corrosion resistance and heat resistance of the glass. In some embodiments of the present application, the 3D heat-bendable microcrystalline glass includes 0.00-2.00 mol%, 0.00-1.50 mol%, 0.00-1.00 mol%, 0.00-0.50 mol%, 0.50-2.00 mol%, 1.00-2.00 mol%, or 1.50-2.00 mol% of P2O5, measured in molar percentage of oxide. In some embodiments of the present application, the 3D heat-bendable glass-ceramics includes 0.20 mol%, 0.50 mol%, 0.80 mol%, 0.90 mol%, 1.00 mol%, 1.30 mol%, 1.50 mol% or 2.00 mol% P2O5 in terms of molar percentage of oxides; or P2O5 within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges.
[0106] Li2O is an essential component of the microcrystalline glass substrate of the present invention, which contributes to the formation of petalite and lithium silicate crystal phases, and is also an essential component for chemical strengthening, which is beneficial to improve the strength, solubility and formability of glass. In some embodiments of the present application, the 3D hot-bendable microcrystalline glass includes 14.00-23.00 mol%, 14.00-22.00 mol%, 14.00-21.00 mol%, 14.00-20.00 mol%, 14.00-19.00 mol%, 15.00-23.00 mol%, 16.00-23.00 mol%, 17.00-23.00 mol%, 18.00-23.00 mol%, 19.00-23.00 mol% or 20.00-23.00 mol% of Li2O, in terms of molar percentage of oxide. In some embodiments of the present application, the 3D heat-bendable glass-ceramics includes 14.00 mol%, 15.00 mol%, 16.00 mol%, 17.00 mol%, 18.00 mol%, 19.00 mol%, 20.00 mol%, 21.00 mol%, 22.00 mol%, 23.00 mol% or 24.00 mol% Li2O, or Li2O within a numerical range consisting of any two of the above specific values as endpoints, in terms of molar percentage of oxide. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0107] ZrO2 can improve the viscosity, hardness, elastic modulus, refractive index, chemical stability of glass and reduce the thermal expansion coefficient of glass. In some embodiments of the present application, the 3D heat-bendable microcrystalline glass includes 1.00-3.00mol%, 1.50-3.00mol%, 2.00-3.00mol%, 1.00-2.50mol% or 1.00-2.00mol% ZrO2 in terms of molar percentage of oxide. In some embodiments of the present application, the 3D heat-bendable glass-ceramics includes 0.50 mol%, 1.00 mol%, 1.50 mol%, 1.70 mol%, 1.8 mol%, 1.90 mol%, 2.00 mol%, 2.10 mol%, 2.20 mol%, 2.30 mol%, 2.40 mol%, 2.50 mol%, 2.60 mol%, 2.70 mol% or 3.00 mol% ZrO2, or ZrO2 within a numerical range consisting of any two of the above specific values as endpoints, in terms of molar percentage of oxide. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0108] Na2O is an oxide outside the glass network, which can provide free oxygen to increase the oxygen-silicon ratio in the glass structure, and play a role in adjusting the grain size. In some embodiments of the present application, the 3D heat-bendable microcrystalline glass includes 0.10-4.00 mol%, 0.50-4.00 mol%, 1.00-4.00 mol%, 1.50-4.00 mol%, 2.00-4.00 mol%, 3.00-4.00 mol%, 0.10-3.50 mol%, 0.10-3.00 mol%, 0.10-2.50 mol%, 0.10-2.00 mol%, 0.10-1.50 mol% or 0.10-1.00 mol% Na2O in terms of the molar percentage of the oxide. In some embodiments of the present application, the 3D heat-bendable glass-ceramics includes 0.10 mol%, 0.20 mol%, 0.30 mol%, 1.00 mol%, 1.10 mol%, 1.50 mol%, 1.60 mol%, 1.90 mol%, 2.00 mol%, 2.50 mol%, 2.90 mol%, 3.00 mol%, 3.10 mol%, 3.50 mol%, 3.60 mol% or 4.00 mol% of Na2O, or Na2O within a numerical range consisting of any two of the above specific values as endpoints, in terms of molar percentage of oxide. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0109] K2O is a network exosome oxide, and the addition of K2O helps to improve the low-temperature melting and formability of the substrate glass. In some embodiments of the present application, the 3D heat-bendable microcrystalline glass includes 0.00-1.00mol%, 0.00-0.80mol%, 0.00-0.50mol%, 0.10-1.00mol%, 0.20-1.00mol% or 0.50-1.00mol% K2O, measured by the molar percentage of the oxide. In some embodiments of the present application, the 3D heat-bendable microcrystalline glass includes 0.10mol%, 0.20mol%, 0.50mol% or 1.00mol% K2O, measured by the molar percentage of the oxide; or K2O within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0110] B2O3 can improve the physical and chemical properties of glass, while reducing the melting point and viscosity of glass and improving the transparency of glass. In some embodiments of the present application, the 3D heat-bendable microcrystalline glass includes 0.10-5.00mol%, 0.50-5.00mol%, 1.00-5.00mol%, 1.50-5.00mol%, 2.00-5.00mol%, 2.50-5.00mol%, 3.00-5.00mol%, 0.10-4.50mol%, 0.10-4.00mol%, 0.10-3.50mol%, 0.10-3.00mol%, 0.10-2.50mol% or 0.10-2.00mol% B2O3, in terms of the molar percentage of the oxide. In some embodiments of the present application, the 3D heat-bendable glass-ceramics includes 0.10 mol%, 0.20 mol%, 0.30 mol%, 1.00 mol%, 1.50 mol%, 1.60 mol%, 1.90 mol%, 2.00 mol%, 2.50 mol%, 2.60 mol%, 2.90 mol%, 3.00 mol%, 3.50 mol%, 3.80 mol%, 3.90 mol% or 4.00 mol% B2O3, or B2O3 within a numerical range consisting of any two of the above specific values as endpoints, in terms of molar percentage of oxide. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0111] CaO can increase the chemical stability and mechanical strength of glass, reduce the viscosity of glass, and improve the solubility and formability of glass. In some embodiments of the present application, the 3D heat-bendable microcrystalline glass includes 0.00-1.50mol%, 0.00-1.00mol%, 0.00-0.50mol%, 0.20-1.50mol%, 0.5-1.50mol% or 1.00-1.50mol% of CaO in terms of the molar percentage of oxide. In some embodiments of the present application, the 3D heat-bendable microcrystalline glass includes 0.10mol%, 0.30mol%, 0.40mol%, 0.50mol%, 0.70mol%, 0.80mol%, 1.00mol%, 1.10mol%, 1.20mol%, 1.30mol% or 1.50mol% of CaO in terms of the molar percentage of oxide; or CaO in the numerical range consisting of any two of the above specific values as endpoints. It should be understood that in specific embodiments, any of the above ranges may be combined with any other ranges.
[0112] In some embodiments of the present application, the 3D bendable glass-ceramic is subjected to a 3D bend process while continuing to crystallize, and after 3D bend, the total crystalline content is 60-90%. In some embodiments of the present application, the 3D bendable glass-ceramic is subjected to a 3D bend process at a temperature of 810°C.
[0113] After 3D heat bending, the total crystalline content of the 3D heat-bendable glass-ceramics can be 60%, 65%, 68%, 70%, 73%, 75%, 78%, 80%, 83%, 85%, 87%, 89% or 90%, or within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0114] In some embodiments of the present application, after 3D hot bending, the sum of the contents of the petalite crystal phase and the lithium disilicate crystal phase of the 3D hot-bendable microcrystalline glass accounts for 45-60% of the total crystal phase content, and the content of the quartz crystal phase accounts for 15-22% of the total crystal phase content; preferably, after 3D hot bending, the sum of the contents of the petalite crystal phase and the lithium disilicate crystal phase of the 3D hot-bendable microcrystalline glass accounts for 45-55% of the total crystal phase content, and the content of the quartz crystal phase accounts for 15-20% of the total crystal phase content.
[0115] In some embodiments of the present application, the 3D heat-bendable microcrystalline glass further includes a lithium silicate (Li2SiO3) crystal phase after 3D heat bending. In some embodiments of the present application, the content of the lithium silicate (Li2SiO3) crystal phase may account for 20-40%, 22-38%, 22-36%, 22-34%, 22-32%, 22-30%, 24-40%, 26-40%, 28-40% or 30-40% of the total crystal phase content. In some embodiments of the present application, the content of the lithium silicate (Li2SiO3) crystal phase may account for 20%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 34%, 36%, 38% or 40% of the total crystal phase content; or it is within the numerical range consisting of any two of the above specific values as endpoints. It should be understood that in specific embodiments, any of the above ranges may be combined with any other ranges.
[0116] In some embodiments of the present application, the 3D heat-bendable microcrystalline glass further includes a spodumene (LiAlSi2O6) crystal phase after 3D heat bending. In some embodiments of the present application, the content of the spodumene (LiAlSi2O6) crystal phase may account for 0-15%, 1-15%, 3-15%, 5-14%, 3-10% or 6-9% of the total crystal phase content. In some embodiments of the present application, the content of the spodumene (LiAlSi2O6) crystal phase may account for 0%, 2%, 3%, 5%, 8%, 10%, 12%, 14% or 15% of the total crystal phase content; or it is within the numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0117] In some embodiments of the present application, the 3D heat-bendable glass-ceramics has an average grain size of 35-50nm, preferably 35-48nm, after 3D heat bending. In some embodiments of the present application, the 3D heat-bendable glass-ceramics has an average grain size of 35nm, 37nm, 38nm, 40nm, 42nm, 43nm, 44nm, 45nm, 46nm, 47nm, 48nm, 49nm or 50nm, or is within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges.
[0118] In a second aspect, the present application provides a method for preparing the 3D heat-bendable glass-ceramics as described above, comprising the following steps:
[0119] Step 1: Mix and melt the raw material components for preparing the substrate glass, and after forming, cool and anneal the mixture to obtain the substrate glass;
[0120] Step 2: Perform nucleation and crystallization treatments on the substrate glass obtained in step 1 to obtain 3D heat-bendable microcrystalline glass.
[0121] In the preparation method of the present application, in step 1, the raw material components for preparing the substrate glass also include a clarifier, and the clarifier includes one or more of NaCl, Na2SO4, SnO2, As2O3, Sb2O3, NaNO3, KNO3, CeO2 and (NH4)2SO4; preferably one or more of NaCl, SnO2, NaNO3 and CeO2.
[0122] In the preparation method of the present application, in step 1, the melting temperature is 1350-1700°C, preferably the melting temperature is 1400-1650°C, and more preferably the temperature is cooled to 500-1000°C after melting.
[0123] In the preparation method of the present application, in step 2, the temperature of the nucleation treatment is 520-590°C, and preferably, the time of the nucleation treatment is 30-600 minutes. In the preparation method of the present application, in step 2, the temperature of the nucleation treatment can be 520°C, 540°C, 550°C, 560°C, 570°C, 580°C or 590°C, or within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges. In the preparation method of the present application, in step 2, the time of the nucleation treatment can be 30 min, 60 min, 90 min, 100 min, 120 min, 150 min, 180 min, 200 min, 250 min, 280 min, 300 min, 350 min, 380 min, 400 min, 450 min, 480 min, 500 min, 550 min, 580 min or 600 min, or within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0124] In some embodiments of the present application, in step 3, the temperature of the crystallization treatment is 640-750°C, and preferably, the time of the crystallization treatment is 20 to 600 minutes. In the preparation method of the present application, in step 3, the temperature of the crystallization treatment can be 640°C, 680°C, 690°C, 700°C, 720°C, 740°C or 750°C, or within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges. In the preparation method of the present application, in step 3, the time of the crystallization treatment can be 20min, 60min, 90min, 100min, 120min, 150min, 180min, 200min, 250min, 280min, 300min, 350min, 380min, 400min, 450min, 480min, 500min, 550min, 580min or 600min, or within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0125] In a third aspect, the present application provides a 3D microcrystalline glass, which is prepared by a 3D heat bending process through the microcrystalline glass that can be 3D hot-bent as described above or the microcrystalline glass that can be 3D hot-bent prepared by the preparation method of the microcrystalline glass that can be 3D hot-bent as described above.
[0126] In some embodiments of the present application, the 3D microcrystalline glass includes a petalite crystal phase, a lithium disilicate crystal phase and a quartz crystal phase, and its total crystal phase content is 60-90%, wherein the sum of the contents of the petalite crystal phase and the lithium disilicate crystal phase accounts for 45-60% of the total crystal phase content, and the content of the quartz crystal phase accounts for 15-22% of the total crystal phase content.
[0127] In some embodiments of the present application, the total crystalline content of the 3D glass-ceramics may be 60%, 65%, 68%, 70%, 73%, 75%, 78%, 80%, 83%, 85%, 87%, 89% or 90%, or within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in specific embodiments, any of the above ranges may be combined with any other ranges.
[0128] In some embodiments of the present application, the 3D glass-ceramics contains petalite (LiAlSi4O 10 ) crystalline phase and lithium disilicate (Li2Si2O5) crystalline phase may account for 45-60%, 48-60%, 50-60%, 45-58%, 46-55%, 45-50% or 55-60% of the total crystalline phase content. In some embodiments of the present application, petalite (LiAlSi4O 10 ) and lithium disilicate (Li2Si2O5) may account for 45%, 48%, 50%, 52%, 54%, 55%, 56%, 57%, 58%, 59% or 60% of the total crystalline phase content, or be within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges.
[0129] In some embodiments of the present application, the quartz crystal phase is β-quartz. In some embodiments of the present application, the content of the quartz crystal phase in the 3D microcrystalline glass may account for 15-22%, 15-20%, 15-18%, 16-22% or 16-20% of the total crystal phase content. In some embodiments of the present application, the content of the quartz crystal phase may account for 15%, 16%, 17%, 18%, 19%, 20% or 22% of the total crystal phase content, or be within the numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0130] In some embodiments of the present application, the 3D microcrystalline glass also includes a lithium silicate (Li2SiO3) crystal phase. In some embodiments of the present application, the content of the lithium silicate (Li2SiO3) crystal phase may account for 20-40%, 22-38%, 22-36%, 22-34%, 22-32%, 22-30%, 24-40%, 26-40%, 28-40% or 30-40% of the total crystal phase content. In some embodiments of the present application, the content of the lithium silicate (Li2SiO3) crystal phase may account for 20%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 34%, 36%, 38% or 40% of the total crystal phase content; or within the numerical range consisting of any two of the above specific values as endpoints. It should be understood that in specific embodiments, any of the above ranges may be combined with any other ranges.
[0131] In some embodiments of the present application, the 3D microcrystalline glass also includes a spodumene (LiAlSi2O6) crystal phase. In some embodiments of the present application, the content of the spodumene (LiAlSi2O6) crystal phase may account for 0-15%, 1-15%, 3-15%, 5-14%, 3-10% or 6-9% of the total crystal phase content. In some embodiments of the present application, the content of the spodumene (LiAlSi2O6) crystal phase may account for 0%, 2%, 3%, 5%, 8%, 10%, 12%, 14% or 15% of the total crystal phase content; or it is within the numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0132] In some embodiments of the present application, the average grain size of the 3D glass-ceramics is 35-50nm, preferably 35-47nm. In some embodiments of the present application, the average grain size of the 3D glass-ceramics can be 35nm, 37nm, 38nm, 40nm, 42nm, 43nm, 44nm, 45nm, 46nm, 47nm, 48nm, 49nm or 50nm, or within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0133] In the present application, the thickness t of the 3D glass-ceramics is not particularly limited, for example, it can be 0.4 to 2.0 mm; preferably 0.4 to 1.0 mm. In some embodiments of the present application, the thickness t of the 3D glass-ceramics can be 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 2.0 mm, or a range formed by any two of the above values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0134] In some embodiments of the present application, the 3D glass-ceramics has a light transmittance of 15-35% at a wavelength of 550nm when the thickness is 0.60mm. In some embodiments of the present application, the 3D glass-ceramics has a light transmittance of 15%, 17%, 19%, 20%, 23%, 25%, 28%, 30%, 32%, 33% or 35% at a wavelength of 550nm when the thickness is 0.60mm, or is within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges.
[0135] In some embodiments of the present application, the color coordinates of the 3D microcrystalline glass in the reflection mode are: L* is 70-81, a* is -2.60-0.00, and b* is -7-1; preferably, the color coordinates of the 3D microcrystalline glass in the reflection mode are: L* is 72-81, a* is -2.21-0, and b* is -6.60-1; more preferably, the color coordinates of the 3D microcrystalline glass in the reflection mode are: L* is 74-81, a* is -2.00-0, and b* is -6.00-1.
[0136] In some embodiments of the present application, the X-axis shrinkage of the 3D glass-ceramics is less than or equal to 1%, preferably less than or equal to 0.5%, and more preferably less than or equal to 0.49%.
[0137] In some embodiments of the present application, the Y-axis shrinkage of the 3D microcrystalline glass is less than or equal to 0.5%, preferably less than or equal to 0.35%, more preferably less than or equal to 0.30%, and further preferably less than or equal to 0.25%.
[0138] In a fourth aspect, the present application provides a method for preparing the 3D microcrystalline glass as described above, comprising the following steps: preparing 3D microcrystalline glass by subjecting 3D heat-bending microcrystalline glass to 3D heat-bending treatment.
[0139] In the preparation method of the 3D glass-ceramics of the present application, the heat bending process is accompanied by a continuous crystallization process. Preferably, the temperature of the heat bending process is 810°C.
[0140] In a fifth aspect, the present application also provides a 3D microcrystalline glass product, which is obtained by chemically strengthening the 3D microcrystalline glass as described above.
[0141] The present application has no restrictions on the conditions for chemical strengthening, as long as the conditions are common chemical strengthening conditions in the art and can achieve the performance of the present application.
[0142] In a sixth aspect, the present application also provides the use of the 3D heat-bendable microcrystalline glass or 3D microcrystalline glass or 3D microcrystalline glass products as described above in electronic devices, preferably in the casing of electronic devices.
[0143] In some embodiments of the present application, the electronic device includes one or more of a mobile phone, a tablet computer, a laptop computer, a television, and a display device.
[0144] Terminology explanation:
[0145] Base glass: glass that has not been subjected to nucleation, crystallization and strengthening treatments.
[0146] Glass-ceramics: also known as glass ceramics, is a type of solid composite material that contains both glass phase and crystal phase (microcrystalline phase, crystalline phase) and is prepared by targeted and controlled crystallization of the base glass.
[0147] Nucleation: Through heat treatment, the nucleating material in the glass grows small crystal nuclei.
[0148] Crystallization: Glass grows a certain crystal based on the crystal nucleus through heat treatment.
[0149] Devitrification: This refers to the complete loss of the transparent properties of glass due to larger crystals or phase separation in the glass-ceramics / glass-ceramics, making it impossible to see any image on the back through the glass.
[0150] Crystallinity: refers to the percentage of the total mass of the crystalline phase / crystals in the microcrystalline glass to the mass of the microcrystalline glass, that is, the total content of the crystalline phase in the microcrystalline glass.
[0151] L value: represents the specular reflection light (SCI) L value, which indicates the brightness of the material. A positive L value indicates whiteness, and a negative L value indicates blackness.
[0152] a value: represents the a value of specular reflected light, which represents the red and green values of the material. A positive a value indicates that the material is reddish, and a negative a value indicates that the material is greenish.
[0153] b value: used to characterize the yellow-blue value of a material. When the b value is tested with transmitted light, the following is added: The optical b value in the present invention is the transmitted light b value, and a positive optical b value indicates that the material is blue.
[0154] Expansion softening point: The temperature at which glass softens. Mainly refers to the temperature at which the glass begins to soften.
[0155] Deformation: Deformation refers to the amount of deformation of the glass. Any object that changes shape when subjected to external force is called "deformation".
[0156] Primary recrystallization: It is essentially the process of nucleation and growth of new strain-free grains.
[0157] Secondary recrystallization: refers to the abnormal growth of secondary grains based on the grains after the primary recrystallization. Strictly speaking, it is a grain growth process under special conditions, not a primary recrystallization process.
[0158] The glass of the present invention is tested by the following method:
[0159] Differential Scanning Calorimetry (DSC) Testing
[0160] The instrument used was Mettler Toledo TGA / DSC 3+ synchronous thermal analyzer, and the test was carried out in accordance with JY / T0589.5-202. The standard used in the test was α-Al2O3 powder, the container for placing the sample was a platinum crucible, the ambient temperature of the instrument was 24°C, and the air humidity was 40%. The glass was ground and sieved through 200 mesh to obtain the sample to be tested. About 20 mg of the sample was weighed and heated from room temperature to 900°C at a heating rate of 10°C / min under a nitrogen atmosphere to obtain the DSC curve of the sample.
[0161] Test of total crystalline phase content and content of each specific crystalline phase
[0162] The microcrystalline glass sample is crushed and ground into a sample with a particle size of less than 75μm. The microcrystalline glass sample is tested by an X-ray diffractometer to obtain an XRD diffraction peak curve. Then the X-ray diffraction data of the X-ray diffractometer (Shimadzu XRD-6100) test result file (RAW format) is put into the Rietveld refinement software (such as Jade, Maud, High score) for fitting and calculation to obtain the total crystalline phase content and the content of each specific crystalline phase in the microcrystalline glass sample. The X-ray diffractometer used in this application is Shimadzu's XRD-6100. The incident angle range used in the test is 2θ=10~50, the scanning speed is 3° / min, the operating voltage is 40kV, and the operating current is 30mA.
[0163] Average grain size test
[0164] The result data obtained by XRD test can be used to calculate the average grain size of the sample according to the Scherrer formula D = Kλ / (βcosθ). Among them, λ is the X-ray wavelength, λ = 0.154056nm, β is the half-height width of the diffraction peak, K = 0.89, and θ is the Bragg diffraction angle. Specifically, the RAW file (diffraction spectrum) output by the XRD instrument is curve fitted in the Jade software, and Jade outputs a fitting report. According to the angle 2θ value and PeakFWHM value (half-height width of the diffraction peak) corresponding to each diffraction peak in the fitting report, and the Peak FWHM value is converted into radians: β = (FWHM / 180×3.14), the grain size of each diffraction peak is calculated by the Scherrer formula D = Kλ / (βcosθ) and the average value is taken to obtain the average grain size.
[0165] Thickness test
[0166] Determined by laser thickness gauge testing.
[0167] CIE L*a*b* parameter test
[0168] The present invention adopts the spectrophotometer CM-3600A of Konica Minolta of Japan for testing, and is connected to SpectraMagicNX spectrum analysis software. The test results are converted into CIELAB color space coordinates (L*; a*; and b*) in the reflection mode based on D65 light source and 10 degree standard observation angle, and the measurement area is LAV (25.4mm).
[0169] Take 5 pieces of glass under the same conditions for testing, and take the average value of each test result as the L* value, a* value and b* value of the microcrystalline glass.
[0170] Light transmittance test
[0171] The light transmittance of the glass at a wavelength of 550nm was tested using a Shimadzu UV-2000 ultraviolet-visible spectrophotometer. Five pieces of glass under the same conditions were tested, and the average value of the test results was taken as the light transmittance of the glass measured at a wavelength of 550nm.
[0172] Single rod static pressure test
[0173] Place the glass sample to be tested on the bottom ring of the tensile testing machine (LT-850A), start the test software, and set the moving speed of the extrusion rod (rod diameter 8mm, indenter arc radius 10mm) to 50mm / min. Click to start the test, and the extrusion rod will apply force to the center of the glass sample to be tested at the set moving speed until the glass sample cracks and breaks.
[0174] The test software will automatically read the force (N) when the glass sample breaks as the test result.
[0175] Take 10 glass samples under the same conditions for testing, and take the average value of the test results as the average single-rod static pressure strength of the glass samples to be tested.
[0176] Glass expansion softening point test
[0177] The sample was made into a cylinder with a diameter of 5.5 mm and a length of 20 mm, and the sample was tested using a thermal expansion instrument LINSEIS L75VD1000. The test temperature was room temperature to 900°C, and the heating rate was 10°C / min. After the test was completed, the thermal expansion coefficient test curve was output. When the curve began to rise first and then fall with the temperature, the corresponding inflection point temperature was the thermal expansion softening point temperature of the sample.
[0178] The present invention is described in detail below by way of examples and comparative examples.
[0179] Example 1
[0180] (1) According to the formula of Example 1 in Table 1, each raw material component is accurately weighed according to the proportion, and is fully mixed to obtain a mixture, wherein the total weight of each raw material component is 1000 g; the mixture is placed in a platinum crucible, and heated to 1650° C. in a high-temperature melting furnace for melting, and the melting time is 6 hours. After removing bubbles, the glass liquid is poured into a mold for cooling and forming. After cooling to 900° C., the mold is placed in a 500° C. annealing furnace for annealing for 24 hours, and then cooled to room temperature with the furnace to obtain a substrate glass.
[0181] (2) The substrate glass obtained in step (1) is heated to a nucleation temperature at a heating rate of 10°C / min for nucleation treatment; then heated to a crystallization temperature at a heating rate of 10°C / min for crystallization treatment; and a glass brick is obtained. The nucleation temperature, nucleation treatment time, crystallization temperature, and crystallization treatment time are shown in Table 1.
[0182] (3) Cutting and polishing the glass bricks obtained in step (2) to obtain 3D heat-bendable microcrystalline glass with a size of 50 mm×50 mm×0.60 mm.
[0183] The performance of the 3D heat-bendable microcrystalline glass obtained above was tested, and the result data are shown in Table 2-3.
[0184] (4) The 3D hot-bendable microcrystalline glass obtained in step (3) is placed in a 3D hot bending machine for hot bending treatment. The hot bending treatment process includes 3 preheating stations, 3 hot pressing stations and 3 cooling stations; the temperatures of the 3 preheating stations are set to 590°C, 680°C and 810°C respectively, the temperatures and pressures of the 3 hot pressing stations are set to 810°C / 0.40MPa, 810°C / 0.40MPa and 810°C / 0.20MPa respectively, and the temperatures of the 3 cooling stations are set to 810°C, 650°C and 600°C respectively; the residence time of each of the above stations is 90s; and the final 3D microcrystalline glass is obtained.
[0185] The performance of the 3D glass-ceramics obtained above was tested, and the result data are shown in Table 4-5.
[0186] Examples 2-9 and Comparative Examples 1-5 were operated under the same conditions as Example 1, except for the composition of the raw materials for preparing the substrate glass shown in Table 1 and the nucleation and crystallization conditions shown in Table 2.
[0187] The 3D glass-ceramics prepared in Examples 1-9 were chemically strengthened to obtain 3D glass-ceramics products. The specific strengthening process is shown in Table 6.
[0188] Table 1: Substrate glass of Examples 1-9 and Comparative Examples 1-4
[0189]
[0190] Table 2 3D heat-bendable glass-ceramics of Examples 1-9 and Comparative Examples 1-5
[0191]
[0192] Where: A represents LiAlSi4O 10 ; B represents Li2Si2O5; C represents Li2SiO3; D represents β-quartz; E represents LiAlSi2O6.
[0193] Table 3 Performance parameters of 3D heat-bendable microcrystalline glass of Examples 1-9 and Comparative Examples 1-5
[0194]
[0195]
[0196] Table 4 3D glass-ceramics after heat bending and its performance parameters
[0197]
[0198] Where: A represents LiAlSi4O 10; B represents Li2Si2O5; C represents Li2SiO3; D represents β-quartz; E represents LiAlSi2O6.
[0199] Table 5 Performance parameters of 3D glass-ceramics after heat bending
[0200]
[0201] Table 6 Strengthening process conditions and properties of 3D glass-ceramics of Examples 1-9
[0202]
[0203] The thermal expansion coefficient curve of the white microcrystalline glass of Example 3 is as follows Figure 1 As shown by Figure 1 From the thermal expansion coefficient curve, it can be seen that the expansion softening point of the white microcrystalline glass prepared in Example 3 is 676°C.
[0204] The white glass-ceramics prepared in Example 3 after being heat-bent at 810°C is shown in the figure below. Figure 2 As shown in FIG. 2 , the glass-ceramics prepared in Comparative Example 2 after being heat-bent at 810° C. is shown in FIG. Figure 3 As shown by Figure 2 and 3 It can be seen that the 3D curved glass-ceramics prepared in Example 3 has a uniform color and is more pleasing to the eye.
[0205] The scanning electron microscope image of the white glass-ceramics prepared in Example 3 before heat bending is as follows: Figure 4 The scanning electron microscope image of the prepared white glass-ceramics after heat bending at 810°C is shown in Figure 5 As shown. Figure 4 and 5 It can be seen that the grain size of the white microcrystalline glass obtained by the primary crystallization method in Example 3 becomes larger after heat bending at 810°C.
[0206] The scanning electron microscope image of the white glass-ceramics prepared in Comparative Example 2 before heat bending is as follows: Figure 6 As shown in the figure, it can be seen that the grain size of the white microcrystalline glass obtained by secondary crystallization in Comparative Example 2 is relatively large.
[0207] The scanning electron microscope image of the white glass-ceramics prepared in Comparative Example 5 before heat bending is as follows: Figure 7 As shown in the figure, it can be seen that the grain size of the white microcrystalline glass prepared in Comparative Example 5 is relatively small.
[0208] The scanning electron microscope image of the white glass-ceramics prepared in Comparative Example 5 after heat bending is as follows: Figure 8 As shown in the figure, it can be seen that the grain size of the white microcrystalline glass prepared in comparative example 5 becomes slightly larger after being hot-bent at 810°C, and the glass is still transparent.
[0209] The XRD patterns of the white glass-ceramics of Example 3 before and after hot bending are as follows: Fig. 9 As shown by Fig. 9 It can be seen that the white microcrystalline glass of Example 3 contains crystalline phases of petalite, lithium disilicate, lithium silicate and quartz before hot bending, and the white microcrystalline glass of Example 3 has more spodumene crystal phase after hot bending.
[0210] The XRD spectrum of the white glass-ceramics prepared in Comparative Example 2 before hot bending is as follows: Fig.10 As shown, it contains crystalline phases of petalite, lithium disilicate, lithium silicate, quartz and spodumene.
[0211] The XRD patterns of the white glass-ceramics of Comparative Example 5 before and after hot bending are as follows: Fig.11 As shown by Fig.11 It can be seen that the transparent microcrystalline glass of Comparative Example 5 only contains petalite and lithium disilicate crystal phases before and after hot bending.
[0212] It can be seen from Tables 2-4 that the crystalline phases of the 3D hot-bendable microcrystalline glass obtained in Examples 1 to 9 are all petalite, lithium disilicate and quartz, and the sum of the contents of petalite and lithium disilicate accounts for 45-70% of the crystal phase content, the content of quartz crystal phase accounts for 4-10% of the crystal phase content, and the expansion softening point ranges from 600 to 800°C. Therefore, the microcrystalline glass obtained in Examples 1-9 can achieve 3D hot bending at 810°C.
[0213] The 3D hot-bendable microcrystalline glass obtained in Example 1-9 is prepared by primary crystallization to prepare white glass containing quartz crystal phase, in which the sum of the contents of petalite and lithium disilicate accounts for 50-70% of the total crystal phase content, the quartz crystal phase content accounts for 4-10% of the total crystal phase content, the average crystal size ranges from 20 to 32 nm, and at 0.60 mm, L* is 70-82, a* is -4-2, and b* is -12-5, presenting a pleasing white appearance; and after hot bending treatment, the sum of the contents of petalite and lithium disilicate accounts for 45-60% of the total crystal phase content, the quartz crystal phase accounts for 15-22%, the average crystal size ranges from 35-50 nm, at 0.60 mm, L* is 70-81, a* is -2.60-0.00, and b* is -7-1; it also presents a pleasing white appearance.
[0214] In Comparative Examples 1-3, in the white glass prepared by secondary recrystallization, the sum of the contents of petalite and lithium disilicate accounts for 60-70% of the total crystalline phase content, but the proportion of quartz crystal phase is far more than 10%, which makes the thermal expansion softening point of the prepared microcrystalline glass above 810°C, and 3D hot bending cannot be performed at 810°C.
[0215] In Comparative Example 4, the sum of the contents of petalite and lithium disilicate accounts for 96.5% of the crystal phase content, while the quartz crystal phase accounts for only 3.50%, so that the thermal expansion softening point is also much greater than 810°C, and 3D hot bending cannot be performed at 810°C.
[0216] In Comparative Example 5, the sum of the contents of petalite and lithium disilicate accounts for 100% of the crystal phase content, while the quartz crystal phase accounts for 0.00%. The thermal expansion softening point is less than 810°C, and 3D hot bending can be performed at 810°C, but the glass appears non-white before and after hot bending.
[0217] It can be seen from Tables 4-5 that the 3D microcrystalline glass prepared in the embodiments of the present application presents a pleasing white appearance (as can be seen from the L*a*b* value), and its shrinkage on the X-axis is less than or equal to 0.5%, and its shrinkage on the Y-axis is less than or equal to 0.35%, showing good dimensional stability.
[0218] It can be seen from Table 6 that the 3D glass-ceramics prepared in the embodiment of the present application can also obtain excellent mechanical properties with a single-rod static pressure strength greater than 320N after chemical strengthening.
[0219] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A 3D heat-bendable glass-ceramic, characterized in that: The crystalline phases of the 3D heat-bendable microcrystalline glass include petalite crystalline phase, lithium disilicate crystalline phase and quartz crystalline phase. The total crystalline phase content of the 3D heat-bendable microcrystalline glass is 40-70%, wherein the sum of the contents of the petalite crystalline phase and the lithium disilicate crystalline phase accounts for 50-70% of the total crystalline phase content, and the content of the quartz crystalline phase accounts for 4-10% of the total crystalline phase content.
2. The 3D heat-bendable glass-ceramic according to claim 1, characterized in that: The quartz crystal phase is β-quartz; and / or, The 3D heat-bendable glass-ceramics further comprises a lithium silicate crystal phase, and preferably the content of the lithium silicate crystal phase accounts for 20-40% of the total crystal phase content; and / or, The crystal phase of the 3D heat-bendable microcrystalline glass also includes a spodumene crystal phase, and preferably, the content of the spodumene crystal phase accounts for 0-11% of the total crystal phase content.
3. The 3D heat-bendable glass-ceramic according to claim 1 or 2, characterized in that: The grain size of the 3D heat-bendable glass-ceramics is 20-40 nm; And / or, the expansion softening point of the 3D heat-bendable glass-ceramics is less than or equal to 810° C.; And / or, when the 3D heat-bendable glass-ceramics has a thickness of 0.60 mm, the light transmittance at 550 nm is between 30% and 50%; And / or, the color coordinates of the 3D heat-bendable micro-ceramic glass in the reflection mode are: L* is 70 to 82, a* is -4 to 2, and b* is -12 to 5.
4. The 3D heat-bendable glass-ceramic according to any one of claims 1 to 3, characterized in that: The composition, expressed as a molar percentage of oxides, contains: SiO2: 60~73%, Al2O3: 4~6%, P2O5: 0~2%, ZrO2: 1~3%, Na2O: 0.1~4%, K2O: 0~1%, Li2O: 14-23%, CaO: 0~1.5% and B2O3: 0.1~5%.
5. The 3D heat-bendable glass-ceramic according to claim 4, characterized in that: The composition, expressed as a molar percentage of oxides, contains: SiO2: 60~73%, Al2O3: 4~6%, P2O5: 0~2%, ZrO2: 1~3%, Na2O: 1~4%, K2O: 0~1%, Li2O: 14-23%, CaO: 0~1.5% and B2O3: 1~5%.
6. The 3D heat-bendable glass-ceramic according to any one of claims 1 to 5, characterized in that: The 3D heat-bendable microcrystalline glass is prepared by subjecting a substrate glass to nucleation and crystallization treatments.
7. The method for preparing 3D heat-bendable glass-ceramics according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: Step 1: Mix the raw materials for preparing glass, melt them, cool them and perform annealing to obtain the substrate glass; Step 2: performing a nucleation treatment on the substrate glass obtained in step 1; Step 3: Crystallize the substrate glass after nucleation in the above step 2 to obtain the microcrystalline glass that can be 3D hot-bent.
8. The preparation method according to claim 7, characterized in that: In step 1, the melting temperature is 1350-1700°C, preferably the melting temperature is 1400-1650°C, and more preferably the temperature is cooled to 500-1000°C after melting.
9. The preparation method according to claim 7 or 8, characterized in that: In step 2, the temperature of the nucleation treatment is 520-590° C., and the nucleation treatment time is preferably 30-600 min; and / or, In step 3, the temperature of the crystallization treatment is 640-750° C., and the preferred crystallization treatment time is 20-600 min.
10. A 3D glass-ceramic, characterized in that: The 3D heat-bendable glass-ceramic according to any one of claims 1 to 6 or the 3D heat-bendable glass-ceramic obtained by the preparation method according to any one of claims 7 to 9 is prepared by a 3D heat bending process.
11. The 3D glass-ceramics according to claim 10, characterized in that: The 3D microcrystalline glass comprises petalite crystal phase, lithium disilicate crystal phase and quartz crystal phase, and the total crystal phase content is 60-90%, wherein the sum of the content of petalite crystal phase and lithium disilicate crystal phase accounts for 45-60% of the total crystal phase content, and the content of quartz crystal phase accounts for 15-22% of the total crystal phase content.
12. The 3D glass-ceramics according to claim 11, characterized in that: The quartz crystal phase is β-quartz, And / or, the 3D glass-ceramics further comprises a lithium silicate crystal phase, and preferably the content of the lithium silicate crystal phase accounts for 20-40% of the total crystal phase content; And / or, the crystal phase of the 3D glass-ceramics further includes a spodumene crystal phase, and preferably, the content of the spodumene crystal phase accounts for 0-15% of the total crystal phase content.
13. The 3D glass-ceramics according to any one of claims 10 to 12, characterized in that: The grain size of the 3D glass-ceramics is 35-50nm; And / or, when the 3D glass-ceramics has a thickness of 0.60 mm, the light transmittance at 550 nm is between 15% and 35%; And / or, the color coordinates of the 3D glass-ceramics in the reflection mode are: L* is 70 to 81, a* is -2.60 to 0.00, and b* is -7 to 1; And / or, the X-axis shrinkage of the 3D glass-ceramics is less than or equal to 1%, preferably less than or equal to 0.5%; preferably, the Y-axis shrinkage of the 3D glass-ceramics is less than or equal to 0.5%, preferably less than or equal to 0.35%; And / or, the single-rod static pressure strength of the 3D microcrystalline glass is greater than 320N.
14. A 3D glass-ceramic product, characterized in that: The 3D glass-ceramics is obtained by subjecting the 3D glass-ceramics described in any one of claims 10 to 13 to chemical strengthening treatment.
15. An electronic device, comprising the heat-bendable glass-ceramic described in any one of claims 1 to 6, or the heat-bendable glass-ceramic prepared by the preparation method described in any one of claims 7 to 9, or the 3D glass-ceramic described in any one of claims 10 to 13, or the 3D glass-ceramic product described in claim 14; preferably, the electronic device is a mobile phone, a tablet computer, a laptop computer, a television or a display device; more preferably, the heat-bendable glass-ceramic or the 3D glass-ceramic is the outer shell of the electronic device or a part of the outer shell, preferably the back panel or a part of the back panel of the electronic device.
16. Use of the heat-bendable glass-ceramic described in any one of claims 1-6, or the heat-bendable glass-ceramic prepared by the preparation method described in any one of claims 7-9, or the 3D glass-ceramic described in any one of claims 10-13, or the 3D glass-ceramic product described in claim 14 in electronic devices, preferably in the housing of electronic devices, and more preferably in the back panel of mobile phones.
Citation Information
Patent Citations
Crystallized glass raw material as well as preparation method and application thereof
CN114790081A
Glass ceramic cover plate, preparation method, repairing and fingerprint resisting method and electronic equipment
CN115477473A
Transparent microcrystalline glass as well as preparation method and application thereof
CN116102260A
Reinforced microcrystalline glass as well as preparation method and application thereof
CN117466534A
Rotary uneven fastening vascular anastomosis device
KR1020250140967A
Cited By
3D hot-bendable glass ceramic, and preparation method therefor and use thereof
WO2025214373A1